Pengaruh Sistem Web Check-In Terhadap Kepuasan Penumpang Maskapai Citilink Di Bandar Udara Abdulrachman Saleh Malang - Riza Prilia Mayasopa; Annike Resty Putrie (Universitas Katolik Widya Karya Malang, 2023)
The existence of a web check-in system facility provided by Citilink airline is one of the company's efforts to reduce complaints from passengers during the check-in process. Where many passengers have to stand for a long time to queue at the check-in counter. So that passengers feel tired and inefficient in the use of time. The purpose of this study is to obtain information about the effect of the web check-in system on Citilink airline passenger satisfaction at Abdulrachman Saleh Airport Malang in April - July 2023. In this study using quantitative research methods. In this study, primary data were used in the form of questionnaires distributed to Citilink airline passengers at Abdulrachman Saleh Airport, Malang with a total of 100 respondents. Secondary data was obtained from documentation in the form of data related to thesis preparation and literature study in the form of looking at previous guidelines. In analyzing the data, the instruments used are validity test, reliability test, normality test, simple linear regression test, T test and coefficient of determination test (R2). From the data analysis that has been done, it shows that the web check-in system has a positive and significant effect on Citilink airline passenger satisfaction at Abdulrachman Saleh Airport, Malang. Based on the results of the R square (R2) determination test, it can be concluded that the web check-in system has a 70.6% effect on Citilink airline passenger satisfaction at Abdulrachman Saleh Airport, Malang. While 29.4% of passenger satisfaction is influenced by other variables not examined. The simple linear regression test produces a constant value of 9.296 which is the consistency value of the passenger satisfaction variable (Y). Then the t test (partial) produces a significant value of 0.000 > 0.05 with a t count > t table (15.228 > 1.66055). The value obtained from the results of hypothesis testing shows that H0 is rejected and Ha is accepted.